HLA class I antigen defects in malignant cells - functional and clinical relevance - Ferrone, Soldano (Henry Stewart Talks, 2015)
HLA class I antigen processing and expression in tumors, HLA class I changes and their impact on tumor cell/immune system interactions, Radiation and chemo therapy enhancement of anti-tumor host immune response, Effects of HLA class I changes on disease clinical course & immune therapy response